THE LEXICAL ERRORS MADE BY THE EIGHTH GRADERS OF SMP PGRI 1 PALEMBANG IN TRANSLATING NARRATIVE TEXT ENTITLED "THE FOX AND THE GRAPES" FROM ENGLISH INTO INDONESIAN - Mastoni; Tahrun; Mulyadi (Esteem Journal of English Education Study Programme, 2024)
The objective of this research aims to know the types, the causes of lexical error found in translating narrative text, and the steps of the implication theory for teaching English as a foreign language. This research used a descriptive qualitative approach with the strategy of Case Study. This research used a descriptive qualitative approach with the strategy of Case Study in which analyzing by describing the lexical errors that student produces in translating narrative text from English into Indonesian. The source of data is the narrative text entitled "The Fox and the Grapes". The data were collected by using review book and interview. Based on the research, the researcher found The errors included Prefix type (5 errors), Misselection (2 errors), Using wrong near-synonym (1 error), semantically determined word selection (28 error). Errors committed due to the learner’s inability to recall, errors caused by confusion between formally similar items. The theoretical implication for language teaching. The finding of this research hopefully can give a contribution to the English teaching and learning process.